Glass Fiber for Improved Behavior of Light Expanded Clay Aggregate Concrete Beams: An Experimental Study (Fracture and Structural Integrity, 2023)
Concrete developed from light expanded clay aggregate (LECA) and glass fiber has good performance, durability, and sustainability. Towards this, the experimental investigation was designed to study cubes, cylinders, and simply supported beams. Four mixtures had LECA volume of 0%, 75%, 85%, and 95% as coarse aggregate replacement and glass fiber content volume of 2% (N, L75, L85, and L95), and the other two mixtures had 75% LECA and glass fiber content of 1% and 1.5% (L75-F1 and L75-F1.5). Results compared to normal concrete showed the weight reduction of samples while adding more glass fiber caused slump reduction in contrast to LECA. Increasing glass fiber volume in the mixture had a negative influence on tensile strength while causing compressive strength enhancement. Moment resistance and energy absorption capacity of L85 were enhanced by 7.5% and 10.3%, respectively. For L75-F1 specimens, the beam stiffness and ductility were enhanced by 14.8% and 14.3%, respectively.
Keywords: energy absorption; glass fiber; LECA; LWC; mechanical properties; strength